Intestinal Microbiota at Engraftment Influence Acute Graft-Versus-Host Disease via the Treg/Th17 Balance in Allo-HSCT Recipients - Han, Lijie; Jin, Hua; Zhou, Lizhi; Zhang, Xin; Fan, Zhiping; Dai, Min; Lin, Qianyun; Huang, Fen; Xuan, Li; Zhang, Haiyan; Liu, Qifa (Frontiers in Immunology, 2018)
Animal models have indicated that intestinal microbiota influence acute graft-versus-host disease (aGVHD) by modulating immune homeostasis. But, in humans, the mechanism by which the microbiota induces aGVHD remains unclear. In this study, we investigated the relationship between the intestinal microbiota and T cell subsets in patients who undergo allogeneic hematopoietic stem cell transplantation (allo-HSCT) to explore the mechanism by which microbiota induced aGVHD. Based on aGVHD, this study was categorized into two groups: grades II-IV aGVHD (aGVHD group, n = 32) and grade 0-I aGVHD (non-aGVHD group, n = 49). The intestinal microbiota was detected by 16S rRNA gene sequencing, and the T cell subsets and histone 3 (H3) acetylation in CD4+ T cells in the peripheral blood was assayed by ﬂow cytometry at the time of engraftment. The aGVHD group had greater low microbial diversity than the non-aGVHD group (56.3% vs. 24.5%, p = 0.004). The bacterial community was depleted of Clostridia (e.g., the Lachnospiraceae and Ruminococcaceae families) and enriched for Gammaproteobacteria (e.g., the Enterobacteriaceae family) in the aGVHD group compared with the non-aGVHD group. The relative abundance of Lachnospiraceae and Ruminococcaceae was positively correlated with the Treg/Th17 ratio counts (r = 0.469 and 0.419; p < 0.001 and < 0.001, respectively). Whereas, Enterobacteriaceae was negatively correlated with the Treg/Th17 ratio (r = -0.277; p = 0.012). The level of acetylated H3 in CD4+ T cells was not only correlated with Lachnospiraceae/Ruminococcaceae but also with the Treg/Th17 ratio (r = 0.354; p = 0.001). In conclusions, our results suggest that decreased Lachnospiraceae and Ruminococcaceae and increased Enterobacteriaceae, correlate with a Treg/Th17 imbalance, which might be through acetylated H3 in CD4+ T cells. These findings suggest that intestinal microbiota might induce aGVHD by influencing the Treg/Th17 balance.